Analyzing the promotion of social skills and values in physical education texts and programmes - Loubna Belabbes; Omar Ben Rakaa; Moulay Smail Hafidi Alaoui (CV Rezki Media, 2025)
Background: Global education systems increasingly emphasize holistic development by integrating social skills and ethical values into curricula, with physical education playing a central role in shaping students' cognitive, emotional, and civic competencies. Objectives: This study examines how educational programs and policy documents promote social skills (e.g., empathy, communication, collaboration, autonomy) and ethical principles, with particular attention to the contribution of physical education in fostering academic achievement and responsible citizenship. Methods: A structured literature review was conducted, applying predefined eligibility criteria and guided by socio-emotional learning and self-determination theory. Forty-five academic and institutional texts (published between 2013 and 2023), including frameworks from UNESCO and the Moroccan Ministry of Education, as well as programs such as PATHS and Second Step, were analyzed across diverse linguistic and cultural contexts, with a primary focus on Morocco. Results: Communication (11.11%; 5/45), autonomy (8.89%; 4/45), and cooperation (8.89%; 4/45) emerged as the most frequently emphasized competencies in both Moroccan and international curricula. Physical education was found to reinforce resilience, leadership, and collaborative skills, whereas empathy (4.44%; 2/45) remained underrepresented—reflecting the prevailing prioritization of technical rather than socio-emotional competencies. Implementation remains constrained by structural barriers, including limited resources and cultural misalignment, despite the legislative support of Morocco's framework law 51-17. Conclusions: Embedding social skills within physical education supports students' holistic development. Achieving meaningful implementation requires: (1) short-term alignment of system-level policies and teacher training, and (2) long-term cultural adaptation of programs supported by measurable monitoring indicators.